(untitled) (International Journal of Natural Sciences, 2011)
Seasonal variation of white spot syndrome virus (WSSV) prevalence in broodstocks shrimp, nauplii and postlarvae were investigated from 2004 to 2006 in Bangladesh by polymerase chain reaction (PCR) assay. There was consistent pattern of fluctuation of WSSV prevalence in broodstocks, nauplii and postlarvae. WSSV fluctuation pattern in three stages were more or less similar for each year. Average lowest prevalence in broodstock was 0% in September and highest was 90% in May-June during the monsoon season in Bangladesh. The WSSV fluctuation patterns for nauplius correlated with broodstock patterns with average lowest prevalence of 0% in September compared to the highest of 40% in July. Similarly, average lowest prevalence of WSSV in postlarvae was 0% in December and highest was 14% in July. It was evident from this study that WSSV prevalence in broodstock, nauplius and postlarvae remained high during the monsoon season and low during the winter season when the water current, salinity and tidal flashing remained more or less stable in the Bay of Bengal in Bangladesh. Key words: Bangladesh; broodstocks; nauplii; postlarvae; seasonal; shrimp; WSSV. DOI: http://dx.doi.org/10.3329/ijns.v1i3.8822 International Journal of Natural Sciences (2011), 1(3):56-61